Faraday Rotation Due to Quantum Anomalous Hall Effect in Cr-Doped (Bi,Sb)2Te3 - Alexey Shuvaev; Lei Pan; Peng Zhang; Kang L. Wang; Andrei Pimenov (Crystals, 2021)
Quantum anomalous Hall effect (QAHE) represents a quantized version of the classical anomalous Hall effect. In the latter case the magnetization takes over the role of magnetic field and induces nonzero off-diagonal elements in the conductivity matrix. In magnetic topological insulators with the band inversion the QAHE can be reached due to quantized conduction channel at the sample edge if the Fermi energy is tuned into the surface magnetic gap. In the static regime the QAHE is seen as a zero-field step in the Hall resistivity. At optical frequencies this step is transformed into a quantized value of the polarization rotation approaching the fine structure constant <semantics>α=e2/2ε0hc≈1/137</semantics>. However, due to material issues the steps reach the predicted values at millikelvin temperatures only. In this work we investigate the Faraday polarization rotation in thin films of Cr-doped topological insulator and in the sub-terahertz frequency range. Well defined polarization rotation steps can be observed in transmittance in Faraday geometry. At temperatures down to <semantics>T=1.85</semantics> K the value of the rotation reached about 20% of the fine structure constant and disappeared completely for <semantics>T>20</semantics> K.